Assessing Objective and Verifiable Indicators Associated With Work-Related Stress: Validation of a Structured Checklist for the Assessment and Management of Work-Related Stress - Barbaranelli, Claudio; Ghezzi, Valerio; Di Tecco, Cristina; Ronchetti, Matteo; Fida, Roberta; Ghelli, Monica; Persechino, Benedetta; Iavicoli, Sergio (Frontiers in Psychology, 2018)
Risk assessment represents an essential part of any successful intervention in health and safety at work. The most prominent European methodologies propose multi-method approaches for identifying the risks associated with work-related stress. Nevertheless, the most widely-used method is the self-administered questionnaire. By adapting the UK Management Standards approach, the Italian National Workers Compensation Authority (INAIL) developed a checklist for the assessment of objective and verifiable indicators of work-related stress. This checklist is filled in by a steering group composed of homogenous groups of workers. Through a web-platform developed by INAIL, a considerable amount of data over the last 5 years has been collected throughout Italy. The aims of this study are to examine the psychometric properties as well as the practical validity of the checklist in a wide sample of Italian companies. The sample comprised 5,301 homogeneous groups of workers nested within 1,631 organisations. The checklist measures two main areas: (1) the organisational indicators of work-related stress (sentinel events) and (2) four and six factors related respectively to content and context of work. Multilevel and multivariate analyses revealed that the checklist shows adequate factor structure and criterion validity. Results also demonstrate that small companies and the public and healthcare sector show higher risk levels. These results support the use of the checklist as a structured and generalizable tool for assessing and monitoring the risks associated with work-related stress.